Analisis Manajemen Risiko pada UMKM Pengolahan Keripik Nanas : Studi Kasus di Desa Kualu Nenas - Vania Palidita Febriana; Tiara Suci Wulandari; Santika Santika; Windi Nuramadani; Linda Hetri Suriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to identify risk management processes and analyze management strategies that can be implemented by Pineapple Chips MSMEs in Kualu Nenas Village. The approach refers to the ISO 31000 framework, which includes risk identification, analysis, evaluation, and management. The results show that the most significant risks are in the high category, especially financial and operational risks, such as fluctuations in raw material prices, product damage due to improper storage, and limited human resources in marketing and production management. To minimize the impact of risks, a thorough analysis and appropriate mitigation strategies are required. The implementation of systematic risk management is considered capable of reducing potential losses, increasing business resilience, and strengthening the position of MSMEs in facing market dynamics. This approach is also crucial in maintaining business continuity, increasing consumer trust, and maintaining business reputation.